2012
DOI: 10.4103/0019-5154.97669
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of suction blister epidermal graft without phototherapy for locally stable and resistant vitiligo

Abstract: Introduction:Surgical methods for treatment of vitiligo include punch grafts, blister grafts, follicular grafts and cultured melanocyte grafts. The aim of this study was to determine the efficacy of suction blister grafts for treatment of vitiligo, without the use of phototherapy.Materials and Methods:This clinical trial study was conducted on 10 patients with vitiligo that was resistant to usual treatments and with limited involvement in the affected sites. We used cryotherapy and a manual suction device for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…in their pilot study on suction blister grafting technique reported complete re-pigmentation in 70% of the cases. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in their pilot study on suction blister grafting technique reported complete re-pigmentation in 70% of the cases. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Stable vitiligo, which is described as vitiligo in which there is no expansion of existing lesions and no appearance of new lesions in the past 1 year,[ 2 3 4 ] can be treated by various surgical procedures. Commonly practised surgical procedures include Thiersch graft,[ 5 6 ] mini graft,[ 7 ] epidermal cellular grafts,[ 8 ] punch grafts, suction blister grafts,[ 9 ] melanocyte culture (MC) and grafting[ 10 ] and autologous non-cultured melanocyte grafting. [ 11 12 ] Non-cultured melanocyte grafting techniques were developed to overcome the time-consuming process of culture while at the same time providing acceptable results.…”
Section: Introductionmentioning
confidence: 99%
“…Blister grafting has shown to given good results even without postgraft phototherapy in other studies too. [ 8 ] With the advent of newer and effective modalities of treatment for stable vitiligo, like autologous melanocyte transfer, the role of relatively older techniques like SBEG has become debatable. However, with our study we would like to reiterate the importance of SBEG as a very effective therapeutic modality for localized and stable vitiligo lesions, especially in the context of resource poor settings.…”
Section: Discussionmentioning
confidence: 99%
“…Maleki et al . [ 22 ] reported that complete repigmentation was observed more in male patients than in female patients treated with SBG, though it was not statistically significant; however, they had a very small sample size of only 10 patients. We observed a similar outcome in our study.…”
Section: Discussionmentioning
confidence: 99%